Addressing Irregular Migration through Principled Programmatic Approaches: Examining the West Africa Route - Seshan, Ganesh K. (2023)
Ganesh K. Seshan VIRTUAL RESEARCH SEMINAR Irregular Migration and Food Security: A View from West Africa Co-organized by IFPRI and World Food Programme (WFP) JUL 20, 2023 - 9:30 TO 11:00AM EDT